Pengaruh Fitur Layanan dan Biaya Administrasi Terhadap Kepuasan Nasabah Menggunakan Mobile Banking pada Bank Syariah Indonesia KC - Destianah Destianah; Hilda Hilda; Fakhrina Fakhrina (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This research used a quantitative method with a sampling technique using the Slovin formula to obtain 95 samples. The data collection technique uses a questionnaire. The research results show that the service feature variable (X1) influences customer satisfaction (Y). The results of the t test for service features on customer satisfaction obtained a value of tcount > ttable (3.429>1.986) and a significance value smaller than probability (0.000 ttable (8.264 > 1.986) and a significance value smaller than probability (0.000 < 0.05), meaning that administration costs have an effect on customer satisfaction. The simultaneous test shows that the fcount value is 114.028 and the ftable value is 3.09 (114.028 > 3.09) with a significance level of 0.000 < 0.05. The conclusion of this research is that service features and administration costs influence customer satisfaction using mobile banking at Bank Syariah Indonesia KC Lahat.